Engineered enzymes for enantioselective nucleophilic aromatic substitutions - Thomas M. Lister; George W. Roberts; Euan J. Hossack; Fei Zhao; Ashleigh J. Burke; Linus O. Johannissen; Florence J. Hardy; Alexander A. V. Millman; David Leys; Igor Larrosa; Anthony P. Green (Nature, 2025)
Abstract Nucleophilic aromatic substitutions (SNAr) are among the most widely used processes in the pharmaceutical and agrochemical industries1–4, allowing convergent assembly of complex molecules through C–C and C–X (X = O, N, S) bond formation. SNAr reactions are typically carried out using forcing conditions, involving polar aprotic solvents, stoichiometric bases and elevated temperatures, which do not allow for control over reaction selectivity. Despite the importance of SNAr chemistry, there are only a handful of selective catalytic methods reported that rely on small organic hydrogen-bonding or phase-transfer catalysts5–11. Here we establish a biocatalytic approach to stereoselective SNAr chemistry by uncovering promiscuous SNAr activity in a designed enzyme featuring an activated arginine12. This activity was optimized over successive rounds of directed evolution to afford an engineered biocatalyst, SNAr1.3, that is 160-fold more efficient than the parent and promotes the coupling of electron-deficient arenes with carbon nucleophiles with near-perfect stereocontrol (>99% enantiomeric excess (e.e.)). SNAr1.3 can operate at a rate of 0.15 s−1, perform more than 4,000 turnovers and can accept a broad range of electrophilic and nucleophilic coupling partners, including those that allow construction of challenging 1,1-diaryl quaternary stereocentres. Biochemical, structural and computational studies provide insights into the catalytic mechanism of SNAr1.3, including the emergence of a halide binding pocket shaped by key catalytic residues Arg124 and Asp125. This study brings a landmark synthetic reaction into the realm of biocatalysis to provide an efficient and versatile platform for catalytic SNAr chemistry.